Study on the Bending Performance of Prefabricated H-Shaped Steel Beams with Different Bolt Hole Types - Xin Zhang; Shenlu Yu; Shuaike Feng; Dawei Fan; Fang Zhang; Han Cao (Buildings, 2024)
This paper investigates the structural performance of a new prefabricated H-shaped steel beam assembled using high-strength bolts under three-point bending. The study evaluates four bolt hole types in five layout schemes through experimental tests. The results show that specimens with standard round holes in both the H-shaped steel and connecting plates exhibited 11% to 30% higher flexural bearing capacity compared to other hole types. Additionally, ANSYS simulations closely matched the experimental results, with a 6% difference. The research results provide important references for the design of prefabricated H-shaped steel beams with different bolt hole types, offering a practical foundation for enhancing the flexural performance of steel beam designs.